Improving the quality of nursing documentation: An action research project - Elisha M. Okaisu; Florence Kalikwani; Grace Wanyana; Minette Coetzee (AOSIS, 2014)
Background: Documentation is an important function of professional nursing practise. In spite of numerous improvement efforts globally, inadequate documentation continues to be reported as nurse authors investigate barriers and challenges.   Objectives: The project aimed to improve nurses' documentation of their patient assessments at the CURE Children's Hospital of Uganda in order to enhance the quality of nursing practise.   Method: An action research methodology, using repeated cycles of planning, intervention, reflection and modification, was used to establish best practise approaches in this context for improving nurses' efficacy in documenting assessments in the patient record. The researchers gathered data from chart audits, literature reviews and key informant interviews. Through analysis and critical reflection, these data informed three cycles of systems and practise modifications to improve the quality of documentation.   Results: The initial cycle revealed that staff training alone was insufficient to achievethe project goal. To achieve improved documentation, broader changes were necessary, including building a critical mass of competent staff, redesigned orientation and continuing education, documentation form redesign, changes in nurse skill mix, and continuous leadership support.   Conclusion: Improving nursing documentation involved complex challenges in this setting and demanded multiple approaches. Evidence-based practise was the foundation of changes in systems required to produce visible improvement in practise. The involved role of leadership in these efforts was very important.